Albert Einstein : with profiles of Isaac Newton and J. Robert Oppenheimer - Pasachoff, Naomi E.; World Book, Inc. (Chicago : World Book, 2007)
"A biography of Albert Einstein, with profiles of two prominent individuals, who are associated through the influences they had on one another, the successes they achieved, or the goals they worked toward. Includes recommended readings and web sites"--Provided by publisher.
Includes bibliographical references (p. 109) and index.
Keywords: Einstein, Albert, -- 1879-1955.; Newton, Isaac, -- Sir, -- 1642-1727 -- Influence; Oppenheimer, J. Robert, -- 1904-1967.; Physicists -- Biography